Major fatty acids composition of 32 almond (Prunus dulcis [Mill.] D.A. Webb) genotypes distributed in East and Southeast of Anatolia - Karatay, Huseyin; Sahin, Ahmet; Yilmaz, Okkes; Aslan, Abdullah (Walter de Gruyter Gmbh, 2014)
Objective: In this study, the fatty acid compositions of 32 different almond (Prunus dulcis (Mill.) D. A. Webb) genotypes seeds that collected from South and South East Anatolia regions in Turkey were studied. Methods: For lipid extraction of almond genotypes Hara and Radin (1978) method were used. Fatty acids content were determined using gas chromatographic (GC) analysis. The datas were evalulated with SPSS 17.0 statistical program. Results: In the gas chromatographic analysis, palmitic acid (16: 0), palmitoleic acid (16: 1), stearic acid (18: 0), oleic acid (18: 1), linoleic acid (18: 2), and linolenic acid (18: 3) were determined to be 5.34%, 0.70%, 0.85%, 74.46%, 17.89%, and 0.75% respectively. Saturated fatty acids (SFA) 6.19%, unsaturated fatty acids (USFA) 93.81% and a rate of USFA/SFA of 15.40, monounsaturated fatty acids (MUFA) 75.16%, polyunsaturated fatty acids (PUFA) 18.65% and a MUFA/ PUFA ratio of 4.32 were found. In the correlation analysis, the highest correlation coefficient (r=-0.988) was detected between oleic acid and linoleic acid. Relationships among almond samples were partially identified with the cluster analysis. Conclusion: In this study, the variations were found between almond genotypes collected from different locations in terms of fatty acids compositions. Besides, the almond genotypes that have high quality unsaturates fatty acids such as high oleic acids and low linoleik acids content were determened.
Doğu ve Güneydoğu Anadolu’da yayılış gösteren 32 farklı badem (Prunus dulcis [Mill.] D.A. Webb) genotiplerinin başlıca yağ asitleri kompozisyonu
Keywords: Almond; seeds fatty acid composition; correlation; cluster analysis